Examining fault architecture and strain distribution using geospatial and geomechanical modelling: An example from the Qaidam basin, NE Tibet - Pei, Yangwen; Paton, Douglas A.; Knipe, Rob J.; Wu, Kongyou (Marine and petroleum geology, 2017)
The investigation of complex geological setting is still dominated by traditional geo-data collection and analytical techniques, e.g., stratigraphic logging, dip data measurements, structural ground mapping, seismic interpretation, balance section restoration, forward modelling, etc. Despite the advantages of improving our understanding in structural geometry and fault architecture, the geospatial modelling, applying computer-aided three-dimensional geometric design, visualization and interpretation, has rarely been applied to such complex geological setting. This study used the Lenghu fold-and-thrust belt (in Qaidam basin, NE Tibetan Plateau) to demonstrate that the application of geospatial and geomechanical modelling could improve our understanding and provide an effective technique for investigating the fault architecture and strain distribution. The three-dimensional configuration of the Lenghu fold-and-thrust belt was initially derived from traditional analysis techniques, such as regional stratigraphic logging, cross section construction, meso-scale ground mapping and landsat image interpretation. The high-resolution field data and landsat image were integrated to construct the geospatial model, which was subsequently used to quantitatively investigate the fault throw changes along the Lenghu thrust fault zone and to understand its control on the lateral structural variation. The geospatial model was then restored in three dimensions to reveal the kinematic evolution of the Lenghu fold-and-thrust belt. Geomechanical modelling, using a Mass-Spring algorithm, provided an effective three-dimensional tool for structural strain analysis, which was used to predict the strain distribution throughout the overall structure, e.g., normal faults with throws ranging from meters to tens of meters in the hanging-wall. The strain distribution predicted by geomechanical modelling was then validated by the natural normal faults in the hanging-wall. The high accordance between the strain prediction and statistics of natural normal faults demonstrates good applicability of geospatial and geomechanical modelling in the complex geological setting of the Lenghu fold-and-thrust belt. The geospatial models and geomechanical models, therefore, can provide a robust technique for analyzing and interpreting multi-source data within a three-dimensional environment. We anticipate that the application of three-dimensional geospatial modelling and geomechanical modelling, integrating both multi-source geologic data and three-dimensional analytical techniques, can provide an effective workflow for investigating the fault architecture and strain distribution at different scales (e.g., ranging from regional-to meso-scale). •The Lenghu fold-and-thrust belt presents high degree of structural variation.•Geospatial models are constructed based on high-resolution field data.•Uneven fault throw distribution determines the lateral structural variation.•Meso-scale strain distribution is predicted using geomechanical modelling.•Strain prediction needs to be validated by high-resolution field data.